Novel Pyrazine-Bridged D-A-D Type Charge Neutral Probe for Membrane Permeable Long-Term Live Cell Imaging - Liu, Pei; Chen, Suna; Zhao, Wenxuan; Wang, Qiutang; Wu, Shuqi; Xu, Liang; Bai, Dan (Frontiers in Chemistry, 2021)
A novel donor–acceptor–donor (D-A-D) type compound containing pyrazine as the acceptor and triphenylamine as the donor has been designed and synthesized. The photophysical properties and biocompatibility of this probe, namely (OMeTPA)2-Pyr for live cell imaging were systematically investigated, with observed large Stokes shifts, high photostability, and low cytotoxicity. Furthermore, we demonstrated that (OMeTPA)2-Pyr could permeate live cell membranes for labeling. The proposed mechanism of this probe was the binding and shafting through membrane integral transport proteins by electrostatic and hydrophobic interactions. These salient and novel findings can facilitate the strategic design of new pyrazine-fused charge-neutral molecular platforms as fluorescent probes, for long-term in situ dynamic monitoring in live cells.